Problemy tłumaczenia elementów kulturowych. O podejściu interkulturowym w nauczaniu języka obcego przez przekład - Kruk, Agnieszka (Neofilolog, 2023)
Didactic translations and translation projects are one of the ways of familiarising students simultaneously with a foreign language and culture, allowing them to develop language competences and learn about cultural similarities and differences. The aim of this article is to present a way of acquainting students with elements of foreign culture through translation, show the benefits of working with translation for language learning and present difficulties related to the translation of cultural elements and solutions used by translators. Teaching language and culture through translation has many advantages. First of all, working with the original text gives students access to the elements of the source culture in a specific communication context. Moreover, the translation assumes an in-depth understanding of the original, including intercultural allusions and intertextual references. The effort put into the translation process by the students makes them better memorize foreign elements and structures.